2011
DOI: 10.1111/j.1467-9817.2010.01487.x
|View full text |Cite
|
Sign up to set email alerts
|

What we have learned from ‘learning to read in more than one language’

Abstract: Our goal with this special issue was to bring together a range of research on learning to read in more than one language. In this introduction, we provide an overview of clear diversity across the language pairings, learning contexts and reading-related skills examined. We also highlight some particularly noteworthy and often intriguing findings that emerged across the articles. These include the examination of transfer at the skill level, as well as of the direction of the uncovered relationships in time and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…The development of orthographic processing skills in children  .2 Orthographic processing skills across languages Deacon, Wade Woolley and Kirby (2009) recently uncovered cross-language transfer of orthographic processing skills to reading in bilingual children learning to read in English and French, two languages represented with the same Roman alphabet. Lexical orthographic processing skills in one language predicted significant variance in reading outcomes in the other language, after multiple controls, in a bidirectional manner (see also Deacon, Commissaire, Chen & Pasquarella 2013;Deacon, Chen, Luo & Ramirez 2011). These findings differ greatly from those in prior research; several prior studies of bilinguals learning to read two languages in different scripts, such as Chinese and English, have found no correlation between L1 and L2 orthographic processing skills or transfer to reading across languages (Abu Rabia 2001;Arab-Moghaddam & Sénéchal 2001;Gottardo, Yan, Siegel & Wade-Woolley 2001;Wang, Park & Lee 2006).…”
Section: © 2014 John Benjamins Publishing Company All Rights Reservedmentioning
confidence: 82%
See 3 more Smart Citations
“…The development of orthographic processing skills in children  .2 Orthographic processing skills across languages Deacon, Wade Woolley and Kirby (2009) recently uncovered cross-language transfer of orthographic processing skills to reading in bilingual children learning to read in English and French, two languages represented with the same Roman alphabet. Lexical orthographic processing skills in one language predicted significant variance in reading outcomes in the other language, after multiple controls, in a bidirectional manner (see also Deacon, Commissaire, Chen & Pasquarella 2013;Deacon, Chen, Luo & Ramirez 2011). These findings differ greatly from those in prior research; several prior studies of bilinguals learning to read two languages in different scripts, such as Chinese and English, have found no correlation between L1 and L2 orthographic processing skills or transfer to reading across languages (Abu Rabia 2001;Arab-Moghaddam & Sénéchal 2001;Gottardo, Yan, Siegel & Wade-Woolley 2001;Wang, Park & Lee 2006).…”
Section: © 2014 John Benjamins Publishing Company All Rights Reservedmentioning
confidence: 82%
“…In contrast, these relationships were not significant in other samples of bilinguals or second language learners (i.e. older children; see Commissaire, Duncan & Casalis 2011;Deacon, Chen et al 2011). For example, in a study of French-speaking adolescents in grades 6 and 8 who learned English in secondary school, Commissaire and colleagues revealed that only the performance on the lexical measures of orthographic processing was related across languages, after controls for French reading and English vocabulary.…”
Section: © 2014 John Benjamins Publishing Company All Rights Reservedmentioning
confidence: 97%
See 2 more Smart Citations
“…The processes involved in acquiring reading skills in more than one language (or in an AL only) are not fully understood (Deacon and Cain, 2011). Scholars working in the field of bilingual literacy aim to discover whether factors that predict individual reading differences in a L1 also predict reading outcome in a L2/AL, whether metalinguistic knowledge (such as PA) transfer to and assist in the process of acquiring literacy in an AL and whether the phonological structure of a learner's L1 influences phonological development in the AL.…”
Section: Reading In Bilingual Childrenmentioning
confidence: 99%